2021
DOI: 10.21037/apm-21-2324
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the correlation between Helicobacter pylori infection and chronic urticaria

Abstract: Background: A meta-analysis was conducted to examine the correlation between Helicobacter pylori infection and chronic urticaria.Methods: We searched Chinese and English databases, including CNKI, Wanfang, and Weipu, using search terms such as Helicobacter pylori infection, and chronic urticaria for articles published from the establishment of the databases to February 2021 examining the correlation between Helicobacter pylori infection and chronic urticaria. The retrieved articles contained data on Helicobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…A representative sample of 57,779 adults aged 20 years or older were recruited for the study by the national cross-sectional China Pulmonary Health (CPH), which showed that the overall prevalence of allergic rhinitis was 3.06% ( 20 ), which was much lower than our study. In respect of eczema and asthma, our results are similar to those reported by other studies ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…A representative sample of 57,779 adults aged 20 years or older were recruited for the study by the national cross-sectional China Pulmonary Health (CPH), which showed that the overall prevalence of allergic rhinitis was 3.06% ( 20 ), which was much lower than our study. In respect of eczema and asthma, our results are similar to those reported by other studies ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…Another meta-analysis in which 965 CU patients and 1235 controls were involved in 16 clinical trials indicated that, though weakly, the infection of H. pylori is of an obvious effect on the increased risk of CU ( 151 ). A meta-analysis of 1320 patients enrolled by Magen et al showed that the infection of H. pylori was related to the development of CU ( 152 ). Meanwhile, relevant researches have found that the elimination of H. pylori can do help to evaluate the prognosis of CU and may reduce the recurrence rate of chronic urticaria ( 153 , 154 ).…”
Section: Helicobacter Pylori and Autoimmune Diseasesmentioning
confidence: 99%
“…1, 7 Multiple studies have found a positive link between the presence of HP and the development of CU, and the commencement of HP eradication therapy has been shown to be beneficial in reducing symptoms in certain patients. [8][9][10][11][12][13] On the other hand, a number of additional studies have been unable to establish a statistically significant correlation between HP infection and CSU, and the complete eradication of HP has not consistently resulted in the resolution of CSU in all individuals. [14][15][16] Also, a recent meta-analysis reported that CSU patients who received antibiotic therapy for the eradication of HP demonstrated a notably higher rate of CSU remission, regardless of whether HP eradication was achieved or not.…”
Section: Introductionmentioning
confidence: 99%